Use of teriparatide in osteoporotic fracture patients. (January 2016) - Collinge, Cory; Favela, Juan
Abstract: Teriparatide [PTH (1–34)] is a genetically engineered analog of human parathyroid hormone that acts as an anabolic drug by increasing activity in both osteoblasts and osteoclasts. Intermittent (once-daily) doses of teriparatide seem to stimulate osteoblast activity and therefore result in a net increase of bone formation. It is recommended for use in post-menopausal women (PMW), men with hypogonadal osteoporosis, as well as men and women with glucocorticoid-induced osteoporosis. In vivo studies have generated important findings regarding teriparatide's role in the enhancement of fracture healing. The intention of this article is to review the clinical findings of teriparatide to stimulate fracture healing. The drug was shown in a prospective randomized, double blind study to achieve earlier radiographic cortical bridging of three of four cortices (7.4 weeks) compared to patients who were assigned to the placebo group (9.1 weeks). Another study compared mean time for healing and functional outcome in two groups of elderly women who had suffered osteoporotic pelvic fractures: one group received daily 100 μg parathyroid hormone (1–84) injections, while the other group received no treatment. Patients who received the PTH (1–84) injections accelerated radiographic and clinical fracture healing (7.8 weeks) when compared to patients who received no treatment (12.6 weeks, p<0.001). Numerous case series state the safety and potential benefits of teriparatide use in patients recovering from fractures. In the following scenarios, teriparatide might be considered in patients with osteoporosis and a fracture: (1) patients with severe osteoporosis with use of bisphosphonates for a number of years with a fracture not expected to predictably unite, e.g. atypical femur fracture or open tibia fracture, (2) in cases where an osteoporotic patient has failed fracture healing and is considering surgical treatment e.g. non-union surgery. It seems prudent to reevaluate these patients frequently and reconsider which drug class of osteoporotic drug is best for the patient. Finally, it must be stressed that we do not recommend teriparatide in osteoporotic patients that may be well treated with bisphosphonates and a fracture is expected to heal uneventfully, nor when patients with metabolically normal bone have a fracture.